Essays on experimental economics - Castro, Caio de Souza (2024)
This thesis consists of two independent chapters. The first chapter examines the effects of increased access to professional news during Brazil’s 2022 general election. We experimentally provided three-month subscriptions and reading incentives for 1,658 voters recruited on social media. Participants were pre-screened for their interest in news and were free to choose among five prominent outlets across the political spectrum. Participants picked like-minded outlets and shifted their news consumption towards their chosen outlet at the expense of social media. The treatment caused higher news knowledge and increased positive perceptions of professional news, as measured by trust in the outlets and the press. Furthermore, we find important changes in political attitudes, such as increased engagement with the elections and support for democracy. However, the treatment did not sustain increased demand at market prices: two months after the end of the experiment, administrative data shows only three participants subscribed to the newspapers. . The second chapter centers on the Novotec Integrado Program, designed to enhance technical and vocational education offerings in São Paulo, Brazil. This initiative seamlessly integrates technical education into the traditional high school curriculum, aligning with the regulatory reforms established in 2017.Within the public high school system, students have the autonomy to select a specialized field of technical education. During enrollment period in 2021, instances of oversubscription prompted admissions to be determined through a lottery system, facilitating an experimental impact evaluation framework. Our primary objective is to assess the short-term effects of Novotec Integrado on enrolled students in educational outcomes. Specifically, we find positive effects on attendance and the likelihood of the student being promoted to the next academic year, but negative effects on frequency intensity. The frequency volatilty seems to increase. These effects appear to be concentrated among women.